Critical minerals for energy transition and sustainable development in Africa - Antoine Clair; Luc Jacolin; Paul Vertier (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
The ongoing energy transition from fossil fuels to renewable energies could have contrasting effects on African economies, particularly through increased extrac- tion of metals critical to this transition. This paper describes the opportunities and challenges posed by the development of extraction of these metals. While Africa's share of global reserves and production is on the rise, it remains far from its potential. Factors such as lack of investment in transport and governance issues are likely to increase exploration and mining costs on the continent, and hold back the development of the sector. The expected increase in global demand for these critical metals could represent a major source of revenue for producing countries, as well as a diversification opportunity for net fossil fuel exporting countries, provided supply can adjust. The extraction of critical metals can only become a source of sustainable development if it is combined with appropriate fiscal and budgetary policies, controlled management of its social and environmental impacts, and the development of downstream value chains.
Keywords: N17; O13; P48; 330; critical metals; critical minerals; energy transition; Africa